Cobalt-free polycrystalline layered material, composite material, positive plate and battery
Through the design and preparation of the cobalt-free polycrystalline layered material LiNixMnyM1-x-yO2, combined with specific precursors and sintering processes, the high capacity and cycling performance problems of lithium battery materials under high voltage are solved, achieving low cost and high cost The performance of the cathode material significantly improves the cycle stability and electrochemical properties of the battery.
Patent Information
- Application Number
- CN202411286364.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-13
- Publication Date
- 2024-12-17
AI Technical Summary
Developing low-cost and high-performance cobalt-free cathode materials, especially under high voltage conditions, has great challenges because Co elements are highly destructive to the crystal lattice and costly, and the prior art is difficult to contain cobalt without cobalt. Achieve high gram capacity and high cycle performance.
Cobalt-free polycrystalline layered material LiNixMnyM1-x-yO2 is used, where 0.5≤x≤0.6, 0.4≤y≤0.5, 0.9≤x+y≤1, M is selected from Al, Mg, Ti, Zr, W, Y, The elements in B, Nb, Mo, and La are formed through specific precursor preparation and sintering processes to form long sheet particles and spherical particle structures, and a cladding layer is added to the surface of the material to improve the cyclic stability and electrochemistry of the material. performance.
The high capacity, cycle performance and first-time Coulomb efficiency of lithium batteries under high voltage conditions are achieved, which significantly improves the cycle stability and high voltage performance of the battery and reduces material costs.
Smart Images

Figure CN119153680A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium battery materials, and in particular to a cobalt-free polycrystalline layered material, a composite material, a positive electrode sheet and a battery. Background Art
[0002] Lithium-ion battery ternary cathode materials are usually composed of Ni, Co, and Mn (LiNi x Co y Mn 1-x-y O2). The Co element plays an important role in ternary materials. On the one hand, it can effectively inhibit cation mixing, and on the other hand, it can improve electron / ion conductivity, thereby improving electrical performance. Therefore, the development of cobalt-free positive electrode materials is a major challenge. On the other hand, many researchers have found that under high voltage (greater than 4.5V), the Co element in lithium batteries has a strong destructive effect on the crystal lattice, so cobalt-free positive electrode materials can improve high-voltage performance to a certain extent. Moreover, among nickel, cobalt and manganese, the price of Co is the highest, the price of Ni is second, and the price of Mn is the lowest. In order to develop low-cost and high-performance positive electrode materials, low-nickel, cobalt-free and high-voltage positive electrode materials are a major and popular research direction. Summary of the Invention
[0003] The purpose of the present invention is to provide a new polycrystalline layered material that is low in nickel and cobalt-free, has high gram capacity and high cycle performance, can be used as a positive electrode material for the preparation of lithium batteries under high voltage, and enables the battery to have high cycle stability under high voltage conditions.
[0004] In order to achieve the above object, the first aspect of the present invention provides a cobalt-free polycrystalline layered material, the chemical formula of the cobalt-free polycrystalline layered material is LiNi x Mn y M 1-x-y O2, wherein 0.5≤x≤0.6, 0.4≤y≤0.5, and 0.9≤x+y≤1; M is selected from at least one of Al, Mg, Ti, Zr, W, Y, B, Nb, Mo, and La;
[0005] The cobalt-free polycrystalline layered material comprises secondary particles formed by aggregation of primary particles, the primary particles are in the form of long flakes, and the ratio of the longest length to the second longest length of the primary particles is less than 3.5, and the secondary particles are spherical; the width coefficient [(D 90 -D 10 ) / D 50 ] is 0.2-2.
[0006] In some embodiments, the cobalt-free polycrystalline layered material is obtained by mixing a precursor with a lithium source and an optional doping element source and then sintering the mixture.
[0007] In some embodiments, the precursor comprises secondary particles formed by aggregation of primary particles, and the primary particles on the surface of the secondary particles are in the shape of elongated flakes with an aspect ratio greater than 2.
[0008] A second aspect of the present invention provides a composite material, comprising the cobalt-free polycrystalline layered material as described above and a coating layer coated on the surface of the cobalt-free polycrystalline layered material, wherein the coating layer comprises an oxide of at least one element selected from the group consisting of Al, Mg, Ti, Zr, W, Y, B, Nb, Mo, and La; and the coating amount of the coating layer in the composite material is 200-3000 ppm, calculated on the weight of the metal element.
[0009] A third aspect of the present invention provides a positive electrode sheet, which includes a positive electrode current collector and a positive electrode active material layer located on one side surface of the positive electrode current collector, wherein the positive electrode active material layer includes a positive electrode active material, and the positive electrode active material includes the cobalt-free polycrystalline layered material as described above or the composite material as described above.
[0010] A fourth aspect of the present invention provides a battery, comprising the positive electrode sheet as described above.
[0011] The present invention adopts the above technical solution to achieve the following beneficial effects:
[0012] The cobalt-free polycrystalline layered material provided by the present invention can be used as a positive electrode material in high-voltage (greater than 4.5V) lithium batteries. It has the advantages of high gram capacity and high cycle performance. In the case of containing the doping element M, it can effectively improve the cycle stability and ultimately achieve good high-voltage performance. Using this material as a positive electrode material can enable the battery to have high cycle stability, high first coulombic efficiency, and high first discharge specific capacity under high voltage conditions.
[0013] The endpoints and any values of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article. Herein, unless otherwise specified, data ranges include endpoints. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 This is a SEM image of the precursor prepared in Example 1 of the present invention at a magnification of 20,000x;
[0015] Figure 2 This is a SEM image of the precursor prepared in Comparative Example 1 of the present invention at a magnification of 20,000x;
[0016] Figure 3 This is a SEM image of the cobalt-free polycrystalline layered material prepared in Example 1 of the present invention at a magnification of 50,000x;
[0017] Figure 4 This is a SEM image of the cobalt-free polycrystalline layered material prepared in Comparative Example 1 of the present invention at a magnification of 50,000x;
[0018] Figure 5 XRD spectra of the precursors prepared in Example 1 and Comparative Example 1 of the present invention (the lower line corresponds to the precursor in Example 1, and the upper line corresponds to the precursor in Comparative Example 1).
[0019] Figure 6 XRD spectra of the cobalt-free polycrystalline layered materials prepared in Example 1 and Comparative Example 1 of the present invention (the lower line corresponds to the cobalt-free polycrystalline layered material of Example 1, and the upper line corresponds to the cobalt-free polycrystalline layered material of Comparative Example 1). DETAILED DESCRIPTION
[0020] The following is a detailed description of the specific embodiments of the present invention. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention and are not intended to limit the present invention.
[0021] Unless otherwise defined, all scientific and technical terms used in the present invention have the same meanings as commonly understood by one of ordinary skill in the art to which this invention relates.
[0022] The first aspect of the present invention provides a cobalt-free polycrystalline layered material, wherein the chemical formula of the cobalt-free polycrystalline layered material is LiNi x Mn y M 1-x-y O2, wherein 0.5≤x≤0.6 (for example, 0.5, 0.52, 0.54, 0.56, 0.58, 0.6), 0.4≤y≤0.5 (for example, 0.4, 0.42, 0.44, 0.46, 0.48, 0.5), 0.9≤x+y≤1 (for example, 0.9, 0.92, 0.94, 0.96, 0.98, 1); M is selected from at least one of Al, Mg, Ti, Zr, W, Y, B, Nb, Mo, and La;
[0023] The cobalt-free polycrystalline layered material comprises secondary particles formed by aggregation of primary particles, the primary particles are in the form of long flakes, and the ratio of the longest length to the second longest length of the primary particles is less than 3.5 (for example, 1.1, 1.2, 1.4, 1.6, 1.8, 2, 2.2, 2.4, 2.6, 2.8, 3, 3.2, 3.4, 3.5), and the secondary particles are spherical; the width coefficient [(D 90 -D 10 ) / D 50] is 0.2-2 (for example, 0.2, 0.4, 0.6, 0.8, 1, 1.5, 2).
[0024] In the present invention, the width coefficient of the material can be obtained by measuring the particle size.
[0025] For the cobalt-free polycrystalline layered material described in the present invention, when the proportion of nickel element is within this range (0.5≤x≤0.6), it is beneficial for the material to obtain better high-voltage performance.
[0026] In some embodiments, the specific surface area of the cobalt-free polycrystalline layered material is 0.5-2 m 2 / g (for example, 0.5m 2 / g, 0.8m 2 / g、1m 2 / g, 1.2m 2 / g, 1.5m 2 / g, 1.8m 2 / g, 2m 2 The specific surface area can be obtained by BET test.
[0027] In some embodiments, the secondary particles have a particle size Dv50 of 2 μm-5 μm (e.g., 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm). When the secondary particle size is within this range, it is beneficial to increase the compaction density of the material, thereby improving the performance of the battery.
[0028] In the present invention, the particle size of the secondary particles of the material can be measured by a particle size tester.
[0029] In some embodiments, the average particle size of the primary particles is less than 1 μm (e.g., 0.1 μm, 0.2 μm, 0.4 μm, 0.6 μm, 0.8 μm, or 1 μm). When the primary particle size is within this range, the particle size is smaller and the ion diffusion distance is shorter, which is beneficial for significantly improving the charge and discharge depth and improving the rate performance.
[0030] In the present invention, the particle size of the primary particles can be measured by scanning electron microscopy.
[0031] In some embodiments, the XRD pattern of the cobalt-free polycrystalline layered material includes (003) crystal plane, (104) crystal plane, (101) crystal plane, (012) crystal plane, (018) crystal plane, (110) crystal plane, (015) crystal plane, (107) crystal plane and (113) crystal plane, and the peak intensity I of the (003) crystal plane is (003) Maximum, I (104) Second.
[0032] In some embodiments, the diffraction angle 2θ of the (003) crystal plane peak is 18.4 to 18.8°. In some embodiments, the diffraction angle 2θ of the (104) crystal plane peak is 43.8 to 44.2°.
[0033] In some embodiments, I (003) / I (104) It is 1.5-2 (for example, 1.5, 1.6, 1.7, 1.8, 1.9, 2), which indicates that the degree of cation mixing in the material is low.
[0034] In some embodiments, the peaks corresponding to the (006) and (102) crystal planes form a double peak, i.e., they are cleavage peaks. In some embodiments, the peaks corresponding to the (108) and (110) crystal planes form a double peak, i.e., they are cleavage peaks. The presence of these cleavage peaks indicates a good layered structure.
[0035] In some embodiments, the cobalt-free polycrystalline layered material is obtained by mixing a precursor with a lithium source and an optional doping element source and then sintering the mixture.
[0036] In some embodiments, the lithium source comprises at least one of lithium carbonate, lithium hydroxide, and lithium oxalate. The amount of the lithium source can be adjusted as needed. In some embodiments, the ratio of the molar amount of the lithium source to the total molar amount of the metal in the precursor and the doping element source, calculated as the element, is 1.05-1.15.
[0037] In some embodiments, the doping element source is an oxide of M, including but not limited to at least one of Al2O3, MgO, TiO2, ZrO2, WO3, Y2O3, B2O3, Nb2O3, MoO2, and La2O3. The amount of the doping element can be adjusted according to the target product. In some embodiments, the doping amount of the doping element source is such that the M content in the cobalt-free polycrystalline layered material is 200 ppm-10000 ppm, such as 200 ppm, 500 ppm, 1000 ppm, 2000 ppm, 4000 ppm, 6000 ppm, 8000 ppm, or 10000 ppm, preferably 200 ppm-5000 ppm.
[0038] In some embodiments, the sintering includes a first sintering and a second sintering.
[0039] In some embodiments, the first sintering conditions include: a temperature of 300-800°C, such as 300°C, 400°C, 500°C, 600°C, 700°C, and 800°C, and a time of 2-6 hours, such as 2 hours, 3 hours, 4 hours, 5 hours, and 6 hours. In some embodiments, the first sintering temperature rise rate is 3-5°C / min, such as 3°C / min, 3.5°C / min, 4°C / min, 4.5°C / min, and 5°C / min.
[0040] In some embodiments, the second sintering conditions include: a temperature of 900-1100° C., such as 900° C., 950° C., 1000° C., 1050° C., and 1100° C., and a time of 12-36 hours, such as 12 hours, 15 hours, 18 hours, 21 hours, 24 hours, 27 hours, 30 hours, 33 hours, and 36 hours. In some embodiments, the second sintering temperature rise rate is 1-3° C. / min, such as 1° C. / min, 1.5° C. / min, 2° C. / min, 2.5° C. / min, and 3° C. / min.
[0041] In some embodiments, the sintering is performed in an oxygen-containing atmosphere, such as an oxygen atmosphere or a mixed atmosphere of oxygen and nitrogen (such as air). The flow rate of the oxygen or oxygen and nitrogen mixture can be 2-30 L / min. The sintered product can be post-processed, such as crushing and screening.
[0042] In some embodiments, the preparation method of the precursor comprises: contacting a metal salt solution with a strong alkaline solution and an ammonia solution in the presence of oxygen and performing a coprecipitation reaction to obtain the precursor. By introducing oxygen during the coprecipitation process to achieve pre-oxidation of the precursor and refinement of the precursor primary particles, the gram capacity of the cobalt-free polycrystalline layered material can be significantly improved. Further, by optimizing the sintering method and doping with the element M, the capacity and cycle stability of the material can be effectively improved, so that the material has better cycle performance and high voltage performance.
[0043] In some embodiments, the metal comprises Ni, Mn, and optionally M. In the metal salt solution, the solvent may be water, and the solute may be a soluble salt of the metal, such as metal sulfate, nitrate, etc. Those skilled in the art may select the appropriate solution, which will not be described in detail here.
[0044] In some embodiments, the concentration of the metal salt solution is 1 mol / L-4 mol / L. The concentration of each metal can be selected according to the molar ratio of the metal in the target product.
[0045] In some embodiments, the strong base can be KOH and / or NaOH. The concentrations of the strong base and ammonia solution are not particularly limited, as long as they can provide a suitable pH for the reaction. In some embodiments, the concentration of the strong base solution is 1 mol / L to 8 mol / L. The concentration of the ammonia solution is not particularly limited, and commercially available ammonia solution can be used.
[0046] In some embodiments, the coprecipitation reaction temperature is 50-70°C, such as 50°C, 55°C, 60°C, 65°C, 70°C, the initial reaction pH is 11.8-12.2, such as 11.8, 11.9, 12, 12.1, 12.2, and the termination pH is 10.9-11.3.
[0047] In some embodiments, the concentration of NH3 during the reaction is 2-6 g / L.
[0048] In some embodiments, the oxygen is present in the form of a mixture of nitrogen and oxygen.
[0049] In some embodiments, the oxygen content in the mixed gas is 5-20%.
[0050] In some embodiments, the flow rate of the mixed gas is 0.2-5 L / min.
[0051] After the reaction is completed, the precursor can be obtained by solid-liquid separation (such as filtration, centrifugation, etc.), and the impurity content can be reduced by washing and drying.
[0052] In some embodiments, the chemical formula of the precursor is Ni x Mn y M z O a H b , wherein, 0.5≤x≤0.6, 0.4≤y≤0.5, 0≤z≤0.1, 1.75≤a≤2, 1≤b≤2; M is selected from at least one of Al, Mg, Ti, Zr, W, Y, B, Nb, Mo, and La.
[0053] In some embodiments, the precursor comprises secondary particles formed by the aggregation of primary particles, the primary particles on the surface of the secondary particles are in the form of elongated flakes, and the aspect ratio is greater than 2 (for example, 2.1, 2.5, 3, 4, 5 or more), and the secondary particles are spherical. In some embodiments, the length of the primary particles is 0.3 μm-1.5 μm (for example, 0.3 μm, 0.5 μm, 0.8 μm, 1 μm, 1.2 μm, 1.5 μm), and the width is 50 nm-300 nm (for example, 50 nm, 100 nm, 150 nm, 200 nm, 250 nm, 300 nm). The length and width of the primary particles are both measured by the length and width of the primary particles on the surface of the secondary particles, without considering the situation inside the secondary particles. It can be measured by the length and width of the rectangular surface of the primary particles observed at the interface of the SEM image, for example. Figure 1 l and w shown.
[0054] In some embodiments, the particle size Dv50 of the precursor is 1.5 μm-5 μm (for example, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, and 5 μm). The particle size of the cobalt-free polycrystalline layered material is inherited from the precursor. Excessively large particle sizes will increase the charge and discharge impedance and affect the cycle performance, while excessively small particle sizes will affect the compaction density. When the precursor particle size is within this range, the compaction density can be further increased, thereby improving the cycle performance of the material and the cycle capacity and stability of the battery.
[0055] In some embodiments, the width factor of the precursor is 0.2-2, such as 0.2, 0.4, 0.6, 0.8, 1, 1.5, or 2. The narrow distribution of the precursor can maintain a narrow distribution of particle sizes of the cobalt-free polycrystalline layered material, thereby improving the uniformity of the particles, further increasing the compaction density, and thus improving the performance of the battery.
[0056] In some embodiments, the specific surface area of the precursor is 20 to 60 m 2 / g, for example, 20m 2 / g、30m 2 / g, 40m 2 / g, 50m 2 / g, 60m 2 / g.
[0057] In some embodiments, the tap density of the precursor is 1-2.5 g / cm 3 , for example 1g / cm 3 , 1.2g / cm 3 , 1.4g / cm 3 , 1.6g / cm 3 , 1.8g / cm 3, 2g / cm 3 , 2.2g / cm 3 , 2.4g / cm 3 , 2.5g / cm 3 .
[0058] In some embodiments, the precursor XRD diffraction spectrum has peaks at 18.8-19.2°, 36-38.5°, 33-36°, 38.5-41°, and 60.5-63.5°, sorted by peak intensity.
[0059] In some embodiments, the precursor XRD diffraction spectrum has peaks at 18.8-19.2°, 36-38.5°, 33-36°, 38.5-41°, 60.5-63.5°, 45-50.5°, 42-45°, and 65-67.5°, sorted by peak intensity.
[0060] In some embodiments, I 18.8~19.2° / I 36~38.5° It is 5-8, for example, 5, 5.5, 6, 6.5, 7, 7.5, 8. 18.8~19.2° / I 36~38.5 That is, the ratio between the peak intensities at 18.8-19.2° and 36-38.5°.
[0061] In some embodiments, I 33~36° / I 38.5~41° It is 0.8-1.2, for example, 0.8, 0.9, 1, 1.1, 1.2. 33~36° / I 38.5~41° That is, the ratio between the peak intensities at 33-36° and 38.5-41°, which are characteristic peaks of oxidation.
[0062] In some embodiments, the method for preparing the cobalt-free polycrystalline layered material comprises:
[0063] (1) contacting a metal salt solution with a strong base solution and an ammonia solution in the presence of oxygen and performing a coprecipitation reaction to obtain a precursor;
[0064] (2) The precursor is mixed with a lithium source and an optional doping element source and then sintered to obtain the cobalt-free polycrystalline layered material.
[0065] The specific operation method and conditions are as described above and will not be repeated here.
[0066] A second aspect of the present invention provides a composite material, which comprises the cobalt-free polycrystalline layered material as described above and a coating layer coated on the surface of the cobalt-free polycrystalline layered material, wherein the coating layer comprises an oxide of at least one element among Al, Mg, Ti, Zr, W, Y, B, Nb, Mo, and La, and the coating amount of the coating layer in the composite material is 200-3000ppm, calculated by the weight of the metal element.
[0067] In some embodiments, the method for preparing the composite material comprises: mixing the cobalt-free polycrystalline layered material described above with a coating agent and then sintering the mixture.
[0068] In some embodiments, the coating agent is an oxide of M, including but not limited to at least one of Al2O3, MgO, TiO2, ZrO2, WO3, Y2O3, B2O3, Nb2O3, MoO2, and La2O3. The amount of the coating agent can be adjusted according to the target product. In some embodiments, the amount of the coating agent is such that the coating amount of the coating layer in the composite material is 200-3000 ppm, based on the weight of the metal element.
[0069] In some embodiments, the re-sintering conditions include: a temperature of 500-700°C, such as 500°C, 550°C, 600°C, 650°C, or 700°C, and a time of 4-8 hours, such as 4 hours, 5 hours, 6 hours, 7 hours, or 8 hours. In some embodiments, the re-sintering heating rate is 1-6°C / min, such as 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, or 6°C / min.
[0070] A third aspect of the present invention provides a positive electrode sheet, which includes a positive electrode current collector and a positive electrode active material layer located on one side surface of the positive electrode current collector, wherein the positive electrode active material layer includes a positive electrode active material, and the positive electrode active material includes the cobalt-free polycrystalline layered material as described above or the composite material as described above.
[0071] In some embodiments, the positive electrode active material further comprises lithium cobalt oxide, which can be a commercial material with a voltage of 4.5V or above.
[0072] In some embodiments, the particle size Dv50 of the lithium cobalt oxide is 10 μm-20 μm, such as 10 μm, 12 μm, 14 μm, 16 μm, 18 μm, and 20 μm.
[0073] In some embodiments, the ratio of the particle size Dv50 of the cobalt-free polycrystalline layered material to the particle size Dv50 of the lithium cobalt oxide is 0.1-0.4, such as 0.1, 0.2, 0.3, or 0.4. When the particle size ratio is within this range, the compaction density of the electrode can be effectively increased.
[0074] In some embodiments, in the positive electrode active material, the content of cobalt-free polycrystalline layered material is 5-60wt%, such as 5wt%, 10wt%, 20wt%, 30wt%, 40wt%, 50wt%, and 60wt%, and the content of lithium cobaltate is 40-95wt%, such as 40wt%, 50wt%, 60wt%, 70wt%, 80wt%, 90wt%, and 95wt%.
[0075] A fourth aspect of the present invention provides a battery, comprising the positive electrode sheet as described above.
[0076] In some embodiments, the battery is a lithium-ion battery or a lithium metal battery. That is, the battery may use carbon-based materials (such as graphite, carbon black, etc.) and / or silicon-based materials (such as silicon-carbon materials, silicon-oxygen materials, and elemental silicon, etc.) as the negative electrode active material, or lithium metal as the negative electrode active material.
[0077] In some embodiments, the charging cut-off voltage of the battery is above 4.5V.
[0078] Unless otherwise specified, other options for the battery are conventional options in the art. The battery can be assembled in a conventional manner in the art.
[0079] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the embodiments described are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention.
[0080] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.
[0081] The present invention will be described in detail below with reference to specific embodiments. These embodiments are intended to help you understand the present invention but are not intended to limit it.
[0082] Example 1
[0083] This example is used to illustrate the preparation method of cobalt-free polycrystalline layered materials and batteries.
[0084] (1) Preparation of precursor
[0085] A mixed solution containing 1 mol / L nickel sulfate and 1 mol / L manganese sulfate was prepared. At 60°C, the pH of the reaction solution was adjusted to 12.1 and the ammonia concentration to 3 g / L by adding 5 mol / L sodium hydroxide solution and concentrated ammonia solution.
[0086] The mixed solution and sodium hydroxide solution were continuously pumped into the reactor for a coprecipitation reaction. A mixture of air and nitrogen was simultaneously introduced. The pH gradually decreased during the reaction. The ammonia concentration was controlled at 3 g / L throughout the reaction, and the flow rate of the air and nitrogen mixture (air:N2 volume ratio of 1:1) was maintained at 3 L / min. The pH at the reaction endpoint was controlled to be 11.0, and the precursor particle size (Dv50) was controlled to be 3 μm. The resulting precursor was washed with deionized water and thoroughly dried for later use.
[0087] Figure 1 and Figure 5 The SEM image and XRD pattern of the precursor are shown respectively. It can be seen from the figure that the precursor contains secondary particles formed by the aggregation of primary particles. The primary particles on the surface of the secondary particles are slender and flake-like. The secondary particles are spherical. The length of the primary particles is 0.3μm-1μm, the thickness is 50nm-100nm, and the aspect ratio is greater than 2. In the XRD diffraction spectrum of the precursor, peaks are present at 18.8-19.2°, 36-38.5°, 33-36°, 38.5-41°, 60.5-63.5°, 45-50.5°, 42-45°, and 65-67.5° according to the peak intensity. 18.8~19.2° / I 36~38.5° 6.2, I 33~36° / I 38.5~41° is 0.9.
[0088] The particle size Dv50 of the precursor was measured to be 3 μm, the width coefficient was 0.68, and the specific surface area was 34.8 m 2 / g, and the tap density is 1.75g / cm 3 .
[0089] (2) Preparation of cobalt-free polycrystalline layered materials
[0090] The obtained precursor was mixed with lithium carbonate according to a molar ratio of lithium to metal in the precursor of 1.1; the mixture was first sintered at 600°C in an air atmosphere for 4 hours, and then second sintered at 1020°C for 24 hours; the heating rates of the first sintering and the second sintering stages were controlled to be 3°C / min and 1°C / min respectively, and the flow rate of air was 15L / min. After the sintering, the product was passed through a 300-mesh sieve to obtain a cobalt-free polycrystalline layered material LiNi 0.5 Mn 0.5 O2.
[0091] Figure 3 and Figure 6The SEM image and XRD image of the cobalt-free polycrystalline layered material are respectively shown. It can be seen from the figure that the cobalt-free polycrystalline layered material contains secondary particles formed by the aggregation of primary particles. The primary particles are in the form of long flakes, and the ratio of the longest length to the second longest length of the primary particles is 1.5-2.5. The average particle size of the primary particles is 0.8 μm, and the secondary particles are spherical. The XRD image of the cobalt-free polycrystalline layered material contains (003) crystal plane, (104) crystal plane, (101) crystal plane, (012) crystal plane, (018) crystal plane, (110) crystal plane, (015) crystal plane, (107) crystal plane and (113) crystal plane, and the peak intensity I of the (003) crystal plane is 0.8 μm. (003) Maximum, I (104) Secondly, I (003) / I (104) It is 1.54, which indicates that the degree of cation mixing in the material is low; the peaks corresponding to the (006) crystal plane and the (102) crystal plane form a double peak, and the peaks corresponding to the (108) crystal plane and the (110) crystal plane form a double peak, indicating that the layered structure is good.
[0092] It has been determined that the width coefficient of the cobalt-free polycrystalline layered material [(D 90 -D 10 ) / D 50 ] is 0.86, and the specific surface area is 0.94m 2 / g, and the particle size Dv50 of the secondary particles was 3.04 μm.
[0093] (3) Preparation of batteries
[0094] The positive electrode material (a mixture of 20 wt% cobalt-free polycrystalline layered material and 80 wt% lithium cobalt oxide with a particle size of 15.8 μm, Dv50), binder (polyvinylidene fluoride (PVDF), conductive agent (conductive carbon black), and solvent (N-methylpyrrolidone (NMP)) were mixed in a ratio of 90 g:5 g:5 g:200 ml and stirred evenly to form a positive electrode slurry. The slurry was then coated onto aluminum foil, thoroughly dried, and cut into appropriate sizes to form the positive electrode sheets. A lithium metal sheet was used as the negative electrode, and a polypropylene (PP) separator was used as the separator. The electrolyte consisted of 1 mol / L lithium hexafluorophosphate (LiPF6) dissolved in a 1:1 volume ratio of ethylene carbonate (EC) and diethyl carbonate (DEC). The positive electrode, negative electrode, separator, and electrolyte were assembled into a button-type battery in an argon-filled glove box.
[0095] Example 2 group
[0096] The method described in Example 1 was followed, except that the amounts of the components were adjusted and / or the doping element M was added during the preparation of the cobalt-free polycrystalline layered material to prepare materials with different chemical formulas. The chemical formula of the cobalt-free polycrystalline layered material is specifically shown in Table 1.
[0097] Table 1
[0098] serial number Chemical formula Example 1 <![CDATA[LiNi 0.5 Mn 0.5 O2]]> Example 2-1 <![CDATA[LiNi 0.6 Mn 0.4 O2]]> Example 2-2 <![CDATA[LiNi 0.5 Mn 0.499 Al 0.001 O2]]> Example 2-3 <![CDATA[LiNi 0.5 Mn 0.499 You 0.001 O2]]> Examples 2-4 <![CDATA[LiNi 0.5 Mn 0.499 Zr 0.001 O2]]>
[0099] Example 3
[0100] A mixed solution containing 1 mol / L nickel sulfate and 1 mol / L manganese sulfate was prepared. At 55°C, the reaction solution was adjusted to a pH of 12.2 and an ammonia concentration of 5.0 g / L using 5 mol / L sodium hydroxide solution and concentrated ammonia solution. This mixed solution and sodium hydroxide solution were continuously pumped into the reactor for a coprecipitation reaction while a mixture of air and nitrogen was introduced. The pH gradually decreased during the reaction. The ammonia concentration was maintained at 5.0 g / L throughout the reaction, and the air / nitrogen mixture (4:1 volume ratio) was introduced at a rate of 2 L / min. The endpoint pH was controlled at 11.0, and the precursor particle size (Dv50) was maintained at 3.5 μm. The resulting precursor was washed with deionized water and thoroughly dried for later use.
[0101] The obtained precursor was mixed with lithium carbonate according to a molar ratio of lithium to metal in the precursor of 1.12; the mixture was first sintered at 550°C in an air atmosphere for 3 hours, and then second sintered at 1050°C for 18 hours; the heating rates of the first sintering and the second sintering stages were controlled to be 5°C / min and 2.5°C / min respectively, and the flow rate of air was 15 L / min. After the sintering, the product was passed through a 300-mesh sieve to obtain a cobalt-free polycrystalline layered material LiNi 0.5 Mn 0.5 O2.
[0102] The morphology and XRD characteristics of the precursor were determined to be substantially consistent with those of Example 1. The length of the primary particles was 0.5 μm-1 μm, the width was 50-100 nm, and the aspect ratio was greater than 3. The peak positions of the XRD diffraction patterns of the precursor were substantially consistent. 18.8~19.2° / I 36~38.5° is 6.4, I 33~36° / I 38.5~41° The particle size Dv50 of the precursor is about 2 μm, the width coefficient is 0.42, and the specific surface area is 28 m 2 / g, and the tap density is 1.68g / cm 3 .
[0103] The morphology and XRD characteristics of the cobalt-free polycrystalline layered material are basically consistent with those of Example 1. The ratio of the longest length to the second longest length of the primary particles is 1.2-1.8, and the average particle size of the primary particles is 0.9 μm. (003) / I (104) The width coefficient of the cobalt-free polycrystalline layered material [(D 90-D 10 ) / D 50 ] is 0.96, and the specific surface area is 0.83m 2 / g, and the particle size Dv50 of the secondary particles is 4.2 μm.
[0104] Example 4
[0105] A mixed solution containing 1 mol / L nickel sulfate and 1 mol / L manganese sulfate was prepared. At 65°C, the reaction solution was adjusted to a pH of 11.8 and an ammonia concentration of 4.5 g / L using a 6 mol / L sodium hydroxide solution and concentrated ammonia solution. This mixed solution and sodium hydroxide solution were continuously pumped into the reactor for a coprecipitation reaction while a mixture of air and nitrogen was introduced. The pH gradually decreased during the reaction. The ammonia concentration was maintained at 4.5 g / L throughout the reaction, and the air / nitrogen mixture (with a 2:1 volume ratio) was introduced at a rate of 1 L / min. The endpoint pH was controlled at 11.00, and the precursor particle size (Dv50) was maintained at 2.0 μm. The resulting precursor was washed with deionized water and thoroughly dried for later use.
[0106] The obtained precursor was mixed with lithium carbonate at a molar ratio of lithium to metal in the precursor of 1.08; the mixture was first sintered at 450°C in an air atmosphere for 3 hours, and then second sintered at 1000°C for 18 hours; the heating rates of the first sintering and the second sintering stages were controlled to be 5°C / min and 2°C / min, respectively, and the air flow rate was 20 L / min. The sintered product was passed through a 300-mesh sieve to obtain a cobalt-free polycrystalline layered material LiNi 0.5 Mn 0.5 O2.
[0107] The morphology and XRD characteristics of the precursor were determined to be substantially consistent with those of Example 1. The length of the primary particles was 0.5 μm-1 μm, the width was 100-200 nm, and the aspect ratio was greater than 2. The peak positions of the XRD diffraction patterns of the precursor were substantially consistent. 18.8~19.2° / I 36~38.5° is 6.64, I 33~36° / I 38.5~41° The particle size Dv50 of the precursor is 3.5 μm, the width coefficient is 0.46, and the specific surface area is 52 m 2 / g, and the tap density is 1.46g / cm 3 .
[0108] The morphology and XRD characteristics of the cobalt-free polycrystalline layered material are basically consistent with those of Example 1. The ratio of the longest length to the second longest length of the primary particles is 1.8-2.8, and the average particle size of the primary particles is 0.7 μm. (003) / I (104)The width coefficient of the cobalt-free polycrystalline layered material [(D 90 -D 10 ) / D 50 ] is 0.65, and the specific surface area is 1.52m 2 / g, and the particle size Dv50 of the secondary particles is 2.35 μm.
[0109] Example 5
[0110] The operation was carried out according to the method described in Example 1, except that the operating conditions during the preparation of the precursor were different, specifically:
[0111] Example 5-1: The ratio of air to nitrogen introduced during the precursor synthesis process was controlled to be 1:4 (the overall O2 content was 4%).
[0112] The morphology and XRD characteristics of the precursor were determined to be substantially consistent with those of Example 1. The length of the primary particles was 0.6 μm-1.2 μm, the width was 200-400 nm, and the aspect ratio was greater than 3. The peak positions of the XRD diffraction patterns of the precursor were substantially consistent. 18.8~19.2° / I 36~38.5° is 6.6, I 33~36° / I 38.5~41° The particle size Dv50 of the precursor is 3.2 μm, the width coefficient is 0.72, and the specific surface area is 24.9 m 2 / g, and the tap density is 1.81g / cm 3 .
[0113] The morphology and XRD characteristics of the cobalt-free polycrystalline layered material are basically consistent with those of Example 1. The ratio of the longest length to the second longest length of the primary particles is 1.5-2.5, and the average particle size of the primary particles is 0.8 μm. (003) / I (104) The width coefficient of the cobalt-free polycrystalline layered material [(D 90 -D 10 ) / D 50 ] is 0.43, and the specific surface area is 1.06m 2 / g, and the particle size Dv50 of the secondary particles is 3.32 μm.
[0114] Example 5-2: During the precursor synthesis process, the ammonia concentration was controlled to be 6.5 g / L and the initial pH was controlled to be 12.0.
[0115] The morphology and XRD characteristics of the precursor were basically the same as those in Example 1. The length of the primary particles was 0.8 μm-1.5 μm, the width was 200-400 μm, and the aspect ratio was greater than 3. The peak positions of the XRD diffraction patterns of the precursor were basically the same. 18.8~19.2° / I36~38.5° 5.9, I 33~36° / I 38.5~41° The particle size Dv50 of the precursor is 3.4 μm, the width coefficient is 0.57, and the specific surface area is 18.7 m 2 / g, and the tap density is 1.56g / cm 3 .
[0116] The morphology and XRD characteristics of the cobalt-free polycrystalline layered material are basically consistent with those of Example 1. The ratio of the longest length to the second longest length of the primary particles is 1.4-2.1, and the average particle size of the primary particles is 0.9 μm. (003) / I (104) The width coefficient of the cobalt-free polycrystalline layered material [(D 90 -D 10 ) / D 50 ] is 0.76, and the specific surface area is 0.87m 2 / g, and the particle size Dv50 of the secondary particles is 3.23 μm.
[0117] Example 6
[0118] The method described in Example 1 was followed, except that the sintering method during the preparation of the cobalt-free polycrystalline layered material was controlled to be a single sintering, and the sintering conditions included: a temperature of 1020° C., a time of 24 h, and a heating rate of 2.5° C. / min.
[0119] The morphology and XRD characteristics of the cobalt-free polycrystalline layered material were basically consistent with those of Example 1. The ratio of the longest length to the second longest length of the primary particles was 1.5-3, and the average particle size of the primary particles was 0.7 μm. (003) / I (104) The width coefficient of the cobalt-free polycrystalline layered material [(D 90 -D 10 ) / D 50 ] is 0.64, and the specific surface area is 1.34m 2 / g, and the particle size Dv50 of the secondary particles is 3.12 μm.
[0120] Example 7
[0121] The operation is carried out according to the method described in Example 1, except that the prepared cobalt-free polycrystalline layered material is coated with a coating layer and used as the positive electrode material to replace the cobalt-free polycrystalline layered material in Example 1, wherein the method of coating the coating layer is to mix the cobalt-free polycrystalline layered material with a coating agent TiO2 and then re-sinter. The amount of the coating agent is such that the coating amount of the coating layer in the composite material is 1000ppm based on the weight of the metal element. The re-sintering conditions include: temperature of 600°C, time of 5h, and re-sintering heating rate of 5°C / min.
[0122] Comparative Example 1
[0123] The operation was carried out according to the method described in Example 1, except that during the preparation of the precursor, only N2 was introduced during the co-precipitation process, and no air was introduced. The remaining steps were exactly the same.
[0124] Figure 2 and Figure 5 The SEM and XRD patterns of the precursor are shown respectively. It can be seen from the figure that the precursor contains secondary particles formed by the aggregation of primary particles. The primary particles are long strips, and the secondary particles are spherical. The length of the primary particles is 0.5μm-1μm, the width is 0.2-0.4μm, and the aspect ratio is 1.5-4. In the XRD diffraction spectrum of the precursor, characteristic diffraction peaks are found at 18.8-19.2°, 39-42°, 34-36°, 53-55°, etc., sorted by peak intensity, corresponding to Ni and Mn being both divalent Ni. 0.5 Mn 0.5 (OH)2. The width coefficient of the precursor was determined to be 0.63 and the specific surface area was 26.8m 2 / g, and the tap density is 1.65g / cm 3 .
[0125] Figure 4 and Figure 6 The SEM and XRD patterns of the cobalt-free layered material are shown respectively. It can be seen from the figure that the cobalt-free layered material has a single crystal morphology and the primary particles have an irregular convex morphology; the XRD pattern characteristics of the cobalt-free layered material are similar to those of Example 1. It has been determined that the width coefficient [(D 90 -D 10 ) / D 50 ] is 0.97, and the specific surface area is 0.72m 2 / g, and the average particle size of primary particles was 2.74 μm.
[0126] Comparative Example 2
[0127] The operation was carried out in accordance with the method described in Example 1, except that the cobalt-free polycrystalline layered material in Example 1 was replaced by a commercial NCM523 material having the same particle size.
[0128] Comparative Example 3
[0129] The operation was carried out in accordance with the method described in Example 1, except that the cobalt-free polycrystalline layered material in Example 1 was replaced by a commercial NCM613 material having the same particle size.
[0130] Test Case
[0131] The electrochemical performance of the button cells assembled in the examples and comparative examples was tested. The specific test method is as follows. The test results are shown in Table 2.
[0132] The test was conducted using a Wuhan Blue Electric CT2001A battery tester with a charge and discharge voltage range of 3.0V-4.55V. The first discharge specific capacity and first cycle coulombic efficiency at a charge and discharge rate of 0.1C were tested, as was the capacity retention rate after 50 cycles at a charge and discharge rate of 0.5C. Capacity retention rate = discharge specific capacity after 50 cycles / first discharge specific capacity * 100%.
[0133] Table 2
[0134] serial number First discharge specific capacity (mAh / g) First-cycle Coulomb efficiency 0.5C cycle 50T capacity retention rate Example 1 197.83 87.59% 94.53% Example 2-1 198.21 87.35% 94.26% Example 2-2 196.25 88.13% 95.06% Example 2-3 196.72 87.58% 94.73% Examples 2-4 195.63 87.22% 94.78% Example 3 196.55 87.18% 95.23% Example 4 197.25 88.34% 95.56% Example 5-1 194.89 87.23% 94.43% Example 5-2 193.41 87.06% 94.31% Example 6 195.68 87.31% 94.22% Example 7 197.74 88.25% 95.98% Comparative Example 1 192.42 87.13% 92.85% Comparative Example 2 191.19 86.64% 92.85% Comparative Example 3 199.35 86.33% 92.15%
[0135] From the test results of Example 1 and Comparative Example 1, it can be seen that oxidation during the precursor synthesis process can significantly improve the sintering activity of the precursor, so that the specific capacity of the cobalt-free polycrystalline layered material in Example 1 is significantly improved, and the cycle retention rate is also significantly improved.
[0136] From the test results of Example 1, Example 2 and Example 7, it can be seen that element doping or adding a coating layer causes a certain loss in the gram capacity of the material, but can effectively improve the cycle performance.
[0137] From the test results of the embodiment and comparative examples 2 and 3, the cobalt-free layered positive electrode material has better cycle performance at high voltage than the ternary material with the same Ni content, and the low-nickel cobalt-free polycrystalline layered material with 50% Ni content in Example 1 has a gram capacity close to that of the commercial NCM613, i.e., comparative example 3, at a voltage of 4.55V. The cobalt-free layered positive electrode material has better application performance at high voltage.
[0138] In summary, the present invention takes cobalt-free layered materials as the development object, and by introducing a mixed gas of air and nitrogen in a certain proportion during the precursor process, the activity of the precursor is improved, so that the gram capacity and cycle performance of the low-nickel cobalt-free layered polycrystalline positive electrode material obtained after sintering are significantly improved, and it is possible to achieve a gram capacity equivalent to that of commercial NCM613 at a voltage of 4.55V, while having better cycle performance. The cycle performance of the cobalt-free layered material can be further improved by means of element doping and coating. In addition, the cobalt-free layered material can not only be used in pure form, but can also be used in a high-voltage lithium cobalt oxide mixed system. By incorporating a portion of the cobalt-free layered material, the cost can be further reduced without sacrificing gram capacity.
[0139] It should be noted that, in this article, the terms "comprise", "include" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device comprising a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, an element defined by the sentence "comprises a..." does not exclude the presence of other identical elements in the process, method, article or device comprising the element. In addition, it should be pointed out that the scope of the methods and devices in the embodiments of the present invention is not limited to performing functions in the order shown or discussed, and may also include performing functions in a substantially simultaneous manner or in the opposite order according to the functions involved. For example, the described method may be performed in an order different from that described, and various steps may also be added, omitted, or combined. In addition, the features described with reference to certain examples may be combined in other examples.
[0140] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A cobalt-free polycrystalline layered material, characterized in that: The chemical formula of the cobalt-free polycrystalline layered material is LiNi x Mn y M 1-x-y O2, wherein 0.5≤x≤0.6, 0.4≤y≤0.5, 0.9≤x+y≤1; M is selected from at least one of Al, Mg, Ti, Zr, W, Y, B, Nb, Mo, and La; The cobalt-free polycrystalline layered material comprises secondary particles formed by aggregation of primary particles, the primary particles are in the form of long flakes, and the ratio of the longest length to the second longest length of the primary particles is less than 3.5, and the secondary particles are spherical; the width coefficient [(D 90 -D 10 ) / D 50 ] is 0.2-2.
2. The cobalt-free polycrystalline layered material according to claim 1, characterized in that: The specific surface area of the cobalt-free polycrystalline layered material is 0.5-2m 2 / g; and / or The particle size Dv50 of the secondary particles is 2 μm-5 μm; and / or The average particle size of the primary particles is 1 μm or less.
3. The cobalt-free polycrystalline layered material according to claim 1 or 2, characterized in that: The cobalt-free polycrystalline layered material is obtained by mixing a precursor with a lithium source and an optional doping element source and then sintering; Preferably, the doping element source is an oxide of M; Preferably, the lithium source comprises at least one of lithium carbonate, lithium hydroxide and lithium oxalate; Preferably, the sintering includes a first sintering and a second sintering, the conditions of the first sintering include: a temperature of 300-800°C and a time of 3-6 hours; the conditions of the second sintering include: a temperature of 900-1100°C and a time of 12-36 hours; the sintering is performed in an oxygen-containing atmosphere.
4. The cobalt-free polycrystalline layered material according to claim 3, characterized in that: The preparation method of the precursor comprises: contacting a metal salt solution with a strong alkali solution and an ammonia solution in the presence of oxygen and performing a coprecipitation reaction to obtain the precursor; Preferably, the metal comprises Ni, Mn and optionally M; Preferably, the coprecipitation reaction temperature is 50-65°C, the initial reaction pH is 11.8-12.2, and the termination pH is 10.9-11.3; Preferably, the concentration of NH3 during the reaction is 2-6 g / L.
5. The cobalt-free polycrystalline layered material according to claim 4, characterized in that: The oxygen is present in the form of a mixture of nitrogen and oxygen; Preferably, the oxygen content in the mixed gas is 5-20%; Preferably, the amount of the mixed gas introduced is 0.2-5 L / min.
6. The cobalt-free polycrystalline layered material according to any one of claims 3 to 5, characterized in that: The precursor comprises secondary particles formed by aggregation of primary particles, the primary particles on the surface of the secondary particles are in the form of elongated flakes, and the aspect ratio is greater than 2, and the secondary particles are spherical; preferably, the length of the primary particles is 0.3 μm-1.5 μm, and the width is 50 nm-300 nm; The particle size Dv50 of the precursor is 1.5 μm-5 μm; and / or The width coefficient of the precursor is 0.2-2; and / or The specific surface area of the precursor is 20 to 60 m 2 / g; and / or The tap density of the precursor is 1-2.5 g / cm 3 ; and / or In the XRD diffraction spectrum of the precursor, peaks are present at 18.8-19.2°, 36-38.5°, 33-36°, 38.5-41°, and 60.5-63.5° according to the order of peak intensity; Preferably, I 18.8~19.2° / I 36~38.5° 5-8; Preferably, I 33~36° / I 38.5~41° It is 0.7-1.
4.
7. A composite material, characterized in that: The composite material comprises the cobalt-free polycrystalline layered material according to any one of claims 1 to 6 and a coating layer coated on the surface of the cobalt-free polycrystalline layered material, wherein the coating layer comprises an oxide of at least one element selected from the group consisting of Al, Mg, Ti, Zr, W, Y, B, Nb, Mo, and La; and the coating amount of the coating layer in the composite material is 200-3000ppm, based on the weight of the metal element.
8. A positive electrode sheet, characterized in that: The positive electrode sheet comprises a positive electrode current collector and a positive electrode active material layer located on one side surface of the positive electrode current collector, the positive electrode active material layer comprises a positive electrode active material, and the positive electrode active material comprises the cobalt-free polycrystalline layered material according to any one of claims 1 to 6 or the composite material according to claim 7.
9. The positive electrode sheet according to claim 8, characterized in that: The positive electrode active material further comprises lithium cobalt oxide; Preferably, the particle size Dv50 of the lithium cobalt oxide is 10 μm-20 μm; Preferably, the ratio of the particle size Dv50 of the cobalt-free polycrystalline layered material to the particle size Dv50 of the lithium cobalt oxide is 0.1-0.4; Preferably, in the positive electrode active material, the content of the cobalt-free polycrystalline layered material is 5-60wt%, and the content of the lithium cobaltate is 40-95wt%.
10. A battery, characterized in that: The battery comprises the positive electrode sheet according to claim 8 or 9; Preferably, the battery is a lithium ion battery or a lithium metal battery; Preferably, the charging cut-off voltage of the battery is above 4.5V.
Citation Information
Cited By
Positive electrode material and preparation method and application thereof
CN119447287A
Positive electrode active material for lithium-ion secondary batteries, positive electrode for lithium-ion secondary batteries, and lithium-ion secondary batteries
JP2026157747A
Positive electrode material, and preparation method therefor and use thereof
WO2026149444A1
